2020
DOI: 10.1007/s00248-020-01518-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Drivers of Microbial Functioning in Mediterranean Forest Soils

Abstract: Mediterranean forests own distinct characteristics resulting from climate, soil, and vegetation that affect soil microbial communities' assembly and their associated functions. We initiated a multiscalar analysis of environmental drivers of soil functioning to (1) identify pertinent factorial scales and (2) determine the relative importance of soil, vegetation, and geoclimate relative influences in shaping soil microbial functions across the French Mediterranean forests. Soil samples (0-15 cm) were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Similarly, Klimek et al reported that the bacterial CLPP was influenced by nutrient status in the O horizon, but such an effect was not observed in the A horizon in temperate forest soils [ 41 ]. In contrast, significant effects of nutrient status on the bacterial CLPP were observed in pine forest soil [ 5 ] and Mediterranean forest soils [ 42 ]. Hence, the contribution of nutrient status to the CLPP is likely to vary between sites, and factor(s) influencing the CLPP might be site-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Klimek et al reported that the bacterial CLPP was influenced by nutrient status in the O horizon, but such an effect was not observed in the A horizon in temperate forest soils [ 41 ]. In contrast, significant effects of nutrient status on the bacterial CLPP were observed in pine forest soil [ 5 ] and Mediterranean forest soils [ 42 ]. Hence, the contribution of nutrient status to the CLPP is likely to vary between sites, and factor(s) influencing the CLPP might be site-specific.…”
Section: Discussionmentioning
confidence: 99%
“…The changes that took place after fire in the C substrate utilization profiles were almost negligible and ascribed to changes in SOM [54], but they returned to the prefire state in the short term. Both low vulnerability and high resilience have been related to the recovery of vegetation cover and plant composition [65]. The changes detected in the CLPPs were related to time after fire due to the increases in charcoal and ash that promoted soil functionality, changes in phenolic compounds and polymers, and plant recovery [18,66,67], affected by seasonal dynamics [21,68].…”
Section: Discussionmentioning
confidence: 99%
“…Edaphic conditions (mainly pH and P) were the main factors explaining differences in enzymatic profiles among populations of both pine species. Similarly, Brunel, Silva, and Gros (2020) observed that edaphic parameters, and not climate and vegetation, significantly explained microbial functioning patterns in Mediterranean soils. Among their multiple functions, an outstanding feature of ECM fungi is their ability to mobilize nutrients from the soil (Smith & Read, 2008).…”
Section: Structural and Functional Shifts Of Root-tip Ecm Fungal Comentioning
confidence: 91%